Research Status of Perforation Parameter Optimization of Different Well Types at Home and Abroad - Xu, Ke (Scientific Journal of Technology, 2025)
Perforation is a process that penetrates the casing and cement sheath to establish a production channel for oil and gas. Reasonable perforation parameter design is the key to removing contamination and releasing production capacity. Perforation technology can improve the connection between the oil and gas layer and the formation to the greatest extent, thereby significantly increasing the production efficiency of crude oil. Nowadays, perforation technology is widely used in oil and gas field development. Therefore, optimizing perforation parameters is of great significance for improving the production efficiency of oil reservoirs. This paper investigates the current research status of perforation parameter optimization by scholars, and sorts out the research on three types of wells: vertical wells, horizontal wells, and deviated wells respectively.